If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6x = 4x Combine like terms: 2x + -6x = -4x -4x = 4x Solving -4x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4x + -4x = 4x + -4x Combine like terms: -4x + -4x = -8x -8x = 4x + -4x Combine like terms: 4x + -4x = 0 -8x = 0 Divide each side by '-8'. x = 0 Simplifying x = 0
| x-4/5=-1/4 | | X-(0.5x+3.6)=19.6 | | ab^2+(a^2-2b^2)=2ab | | 293=154-v | | c=2c+1 | | 14+6a-18=18 | | 3/4-0.2 | | 7x(3x+5)-11x-6=-16 | | 21(7x)=28(5x+2) | | 0.5x+2.5=10 | | 4s+12t=4 | | 6=18y | | -5s+t=11 | | 13x+10=5x-30 | | 9.54=-2x+2(x+4.77) | | lnx=35.7 | | v^2+4v-10=0 | | 40+19.95x=59.85+29.95x | | 14x(2-3)=xy | | -1/5-1/2v=-1/7 | | 7x^5/x^5 | | 3a+2b+c=n | | 2/3x-5=3 | | x^2+2xy+y^2-9=25 | | 5x^3-13x+20=0 | | (x-3).3+(2x-5).4+4x=0 | | 11x+19y=13 | | (y-24)+(3y-20)= | | 7!/(4)!3! | | 32.475+(4.87*30)= | | 12x/10y*4y/3xy | | 13x+14x+x=57 |